Pharmacological determination of the fractional block of Nav channels required to impair neuronal excitability and ex vivo seizures - Thouta, Samrat; Waldbrook, Matthew G.; Lin, Sophia; Mahadevan, Arjun; Mezeyova, Janette; Soriano, Maegan; Versi, Pareesa; Goodchild, Samuel J.; Parrish, R. Ryley (Frontiers in Cellular Neuroscience, 2022)
Voltage-gated sodium channels (Nav) are essential for the initiation and propagation of action potentials in neurons. Of the nine human channel subtypes, Nav1.1, Nav1.2 and Nav1.6 are prominently expressed in the adult central nervous system (CNS). All three of these sodium channel subtypes are sensitive to block by the neurotoxin tetrodotoxin (TTX), with TTX being almost equipotent on all three subtypes. In the present study we have used TTX to determine the fractional block of Nav channels required to impair action potential firing in pyramidal neurons and reduce network seizure-like activity. Using automated patch-clamp electrophysiology, we first determined the IC50s of TTX on mouse Nav1.1, Nav1.2 and Nav1.6 channels expressed in HEK cells, demonstrating this to be consistent with previously published data on human orthologues. We then compared this data to the potency of block of Nav current measured in pyramidal neurons from neocortical brain slices. Interestingly, we found that it requires nearly 10-fold greater concentration of TTX over the IC50 to induce significant block of action potentials using a current-step protocol. In contrast, concentrations near the IC50 resulted in a significant reduction in AP firing and increase in rheobase using a ramp protocol. Surprisingly, a 20% reduction in action potential generation observed with 3 nM TTX resulted in significant block of seizure-like activity in the 0 Mg2+ model of epilepsy. Additionally, we found that approximately 50% block in pyramidal cell intrinsic excitability is sufficient to completely block all seizure-like events. Furthermore, we also show that the anticonvulsant drug phenytoin blocked seizure-like events in a manner similar to TTX. These data serve as a critical starting point in understanding how fractional block of Nav channels affect intrinsic neuronal excitability and seizure-like activity. It further suggests that seizures can be controlled without significantly compromising intrinsic neuronal activity and determines the required fold over IC50 for novel and clinically relevant Nav channel blockers to produce efficacy and limit side effects.